Increased energy expenditure and fecal fat excretion do not impair weight gain in small-for-gestational-age preterm infants - Böhler, Thomas; Krämer, Thomas; Janecke, Andreas; Hoffmann, Georg F.; Linderkamp, Otwin (Early human development, 1999)
In order to optimize the nutrition of high-risk premature infants beyond the early postnatal period, a more precise knowledge of individual nutritional requirements is needed. We therefore studied the influence of intrauterine growth retardation on energy expenditure and nutrient utilization determined by indirect calorimetry and fecal fat excretion (steatocrit) in nineteen premature infants who were appropriate-for-gestational-age (AGA; mean gestational age 29.9±0.3 weeks, mean birth weight 1.30±0.05 kg) and thirteen small-for-gestational-age (SGA) premature infants [mean gestational age 32.4±0.5 weeks, mean birth weight 1.024±0.07 kg (i.e., below the 10th percentile)] during the first and second month of life. All infants were clinically stable during the study period. In nine SGA infants we observed a significantly higher steatocrit compared to twelve AGA infants (29±1 vs. 17±1% p=0.0001). SGA infants (n=12) also showed a slightly (albeit statistically not significantly) higher energy expenditure than AGA infants (n=15) (58.7±1.9 vs. 53.6±1.5 kcal/kg per day, p=0.054). Despite the increased fat excretion and higher energy expenditure, SGA infants gained weight more rapidly during the study period than AGA infants (20±1 vs. 17±1 g/kg per day, p=0.026). We conclude that influences of intrauterine growth retardation on energy expenditure and nutrient utilization persist during the first weeks of extrauterine life. However, these metabolic changes do not impair the capability of SGA infants for extrauterine catch-up growth if adequate nutrition is provided.